PUTATIVE PRIVATE DEFENCE IN CRIMINAL LAW Tuta v The State 2023 (2) BCLR 179 (CC) - Jolandi Le Roux-Bouwer (Obiter, 2024)
In a country like South Africa, plagued as it is by violent contact crime, it is not surprising that the defences of private defence and putative private defence are often raised by accused in criminal trials. It is trite that, for a conviction in a criminal court, the prosecution is tasked with proving the accused’s liability beyond reasonable doubt. As an element of a crime, unlawfulness does not simply lie in fulfilment of the definitional elements of a crime. There are instances where, notwithstanding fulfilment of the definitional elements of a crime, the conduct is justified or legally regarded as objectively reasonable. These instances are known as grounds of justification and technically serve to exclude unlawfulness. A ground of justification, if successfully raised, is therefore a complete defence to any criminal charge. There is not a numerus clausus of valid grounds of justification in South African criminal law; the test remains whether the accused’s conduct was objectively reasonable in the particular situation. One such ground of justification is private defence. A person acts in private defence, and therefore lawfully, if they use the minimum force necessary to ward off an unlawful human attack that has commenced, or is imminently threatening, upon their or somebody else’s protected legal interests such as life, physical integrity, property, reputation or dignity. The defensive act in private defence must be: necessary to protect the threatened interest; directed at the attacker; reasonably proportionate to the attack; and perpetrated with the knowledge that it is performed in private defence. Unlike private defence, putative private defence is not a ground of justification that excludes unlawfulness. Putative private defence exists where an accused is under the mistaken belief that they are conducting themselves in private defence whereas there is no such ground of justification in the circumstances. If an accused labours under the genuine but erroneous belief in the existence of a ground of justification, their conduct remains unlawful. The accused lacks the knowledge that they are, in reality, acting unlawfully. While the accused’s conduct remains unlawful, the absence of knowledge of unlawfulness results in a lack of intention, since knowledge of unlawfulness is an integral part of intention. The accused’s mistaken belief that they are acting lawfully in private defence must be honest and genuine but need not be rational or reasonable. If, on the facts, there could be no honest and genuine belief on the accused’s part in the lawfulness of their defensive act, putative private defence cannot exist. It is trite that, for private defence to succeed as a ground of justification, the test is objective in the sense that the attack and the defensive action must meet certain objective requirements. The accused’s subjective belief, whatever it may be, has no impact on the validity of private defence as a ground of justification. The Constitutional Court in Tuta v The State (2023 (2) BCLR 179 (CC)) was recently tasked with making a finding on the correct legal test to be applied to the existence of the defence of putative private defence. In this contribution, the Constitutional Court’s decision is analysed.